PUSAT INFORMASI TURIS DI KAMPUNG BATIK BABAGAN LASEM BERBASIS ECO-BATIK - Natalia Lie Leonard; Samsu Hendra Siwi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
This article examines the provision of tourism development facilities in Babagan Batik Village as a tourist information center. Ecological issues are the focus of this research. Kampung Batik Babagan is a home-based batik industry center with scattered batik production houses. This area does not yet have an information center as a forum for tourists to get complete information about the Babagan area. The Babagan Lasem Batik Village Tourist Information Center is designed as an ecological architectural solution in creating an eco-batik ecosystem and as a forum to accommodate and educate tourists and the public regarding information on the historical and cultural values of the Babagan area that are in accordance with the local environmental context. It is hoped that this project can improve the economy of local communities whose main livelihood is from batik by taking into account the impact on the environment. The literature studies used include ecological architecture, eco-batik, textile dyes, and the batik process in Lasem. The research method used is exploratory descriptive method, location and site analysis. From the results of the analysis, the building in the site is divided into two masses according to the function of the activities in it. The roof of the building uses a jurai roof as an adjustment to the tropical climate. The interior of the building is designed to allow interaction between visitors and the exterior is decorated with ornaments that characterize Babagan Batik Village. Keywords:  batik; ecolgy; education; information.AbstrakArtikel ini meneliti tentang penyediaan fasilitas pengembangan pariwisata di Kampung Batik Babagan sebagai pusat informasi turis. Isu ekologis menjadi konsentrasi dalam penelitian ini. Kampung Batik Babagan merupakan sebuah pusat industri batik rumahan dengan letak rumah produksi batik yang tersebar. Di kawasan ini belum memiliki pusat informasi sebagai wadah bagi turis untuk mendapatkan informasi yang lengkap tentang kawasan Babagan. Pusat Informasi Turis Kampung Batik Babagan Lasem dirancang sebagai solusi arsitektur ekologis dalam menciptakan ekosistem eco-batik dan menjadi wadah untuk mengakomodasi serta mengedukasi turis dan masyarakat mengenai informasi nilai sejarah dan budaya dari kawasan Babagan yang sesuai dengan konteks lingkungan setempat. Diharapkan proyek ini dapat meningkatkan ekonomi masyarakat lokal. Kajian literatur yang digunakan meliputi, arsitektur ekologis, eco-batik, zat pewarna tekstil, dan proses pembatikan di Lasem. Metode penelitian yang digunakan, yaitu metode deskriptif eksploratif, analisis lokasi dan tapak. Dari hasil analisis tersebut, bangunan dalam tapak dibagi menjadi dua massa sesuai dengan fungsi kegiatan di dalamnya. Atap bangunan menggunakan atap jurai sebagai penyesuaian dengan iklim tropis. Bagian interior bangunan didesain agar terjadi interaksi antar pengunjung dan pada eksterior diberi ornamen yang mencirikan Kampung Batik Babagan.